Implementation of the Product Environmental Footprint Category Rules for dairy products: An approach to assess nitrogen emissions in a mass balanced dairy farm system. (1st April 2019) - Egas, D.; Vasilaki, V.; Katsou, E.; Stanchev, P.; Ponsá, S.; Colon, J.
Abstract: Following the Single Market for Green Products, the European Commission released the Product Environmental Footprint Category Rules for Dairy Products (PEFCR-D). According to the PEFCR-D, nitrogen (N) emissions must be calculated as stated by The Intergovernmental Panel on Climate Change (IPCC) and the European Environmental Agency (EMEP/EEA) methods. However, since the IPCC method and the EMEP/EEA method follow different N flows, the estimated N emissions differ at common farm stages resulting in incompatibilities in the reported PEFCR-D emissions from a mass balance perspective. This work proposes a comprehensive approach to calculate N emissions to satisfy the PEFCR-D guideline in a N balanced farm system. The proposed approach coordinates and balances the N flows at each stage in order to estimate the N emissions from the dairy system. In this regard, emissions such as N2 O, NH3, NOx, N2 and NO3 − are estimated following the IPCC and EMEP/EEA methods from a single N flow in the system. The N losses in the whole dairy farm are estimated to increase 4.41% as a result of the implementing the PEFCR-D in a N balanced system instead of a non-balanced one. Consequently, an increase in environmental impacts of the farm such as Global Warming Potential (6.68%), Marine Eutrophication (4.91%) and Terrestrial Eutrophication (4.26%) were also measured. Moreover, the proposed approach to implement the PEFCR-D enabled the redistribution of emissions between farm stages; particularly relocating N emissions and environmental impacts between manure management and application. This resulted in a decrement on the manure management stage environmental impacts such as Global Warming (−41.88%) and Photochemical Ozone formation (−25.49%). On the other hand, at application stage, increments in Global Warming (26.94%), Marine Eutrophication (8.48%) and Terrestrial Eutrophication (7.52%) were evidenced when contrasting the outcomes between the non-balanced and balanced PEFCR-D calculation approach.